Automated ultrasound measurements of lateral abdominal muscles under controlled breathing phases. (June 2022) - Mikołajowski, Grzegorz; Pałac, Małgorzata; Linek, Paweł
Highlights: The indirect method of controlling the breathing phases during ultrasound measurement of abdominal muscles is not sufficient. The elasticity of the transversus abdominis seems to be the most vulnerable to changes related to the breathing phase. The device and software developed for this study helps to control the breathing phase during ultrasound measurements. Objective data collection of muscles during inspiration and expiration extends ultrasound application in clinical practice. Abstract: Background and objectives: A breathing phase during ultrasound measurements of the lateral abdominal muscles (LAMs) are usually indirectly controlled by visual inspection of the position of the transversus abdominis (TrA) muscle. This is due to the lack of devices to directly control airflow that are connected to the ultrasound in order to automatically and simultaneously freeze ultrasound images at the programmed breathing phase. Such indirect control may be related with potential measurement error because LAMs are respiratory muscles. Thus, the aim of this study was to present a newly developed and automatic measurement procedure to directly control airflow and at the same time automatically collect ultrasound images at the programed breathing phase. Additionally, it was decided to compare LAMs measurements obtained manually by the examiner and with an external device controlling the peak phase of tidal inspiration and expiration and compare the elasticity and thickness measurements between tidal inspiration and expiration in young participants. Methods: The study was carried out on 10 healthy youth. The thickness and shear modulus were measured by an Aixplorer ultrasound scanner. The measurements were obtained manually by the examiner and with a newly developed external device controlling the peak phases of tidal inspiration and expiration. Results: A significant difference in external/internal oblique thickness between the expiration and inspiration phases depended on the measurement procedure. The TrA thickness was similar during inspiration and expiration. During inspiration, the TrA shear modulus was higher than during expiration, and the TrA shear modulus depended on the measurement procedure. Conclusion: Although the raw LAMs thickness and external/internal oblique thickness/shear modulus data were similar, the measurement procedure may affect the interpretation of the results. The TrA shear modulus is the most vulnerable to errors related to the measurement procedure. Construction of this study device controlling airflow and automatically collecting ultrasound images at the selected breathing phase seems to be promising in future studies considering measurements of respiratory muscles in a strictly defined breathing phase.